# Thread: [SOLVED] Algebra homework - please check if these are right -&gt;

1. ## [SOLVED] Algebra homework - please check if these are right -&gt;

I'm working on my second homework, as I've mentionned before this is a math class I'm taking to get myself up to college math. I'm starting my master's in Human Ress, but I haven't done math since high school, about 20 years ago. My brain just doesn't work as good as it used too?

If someone would just check if those 3 answers are correct, that would be of great help.

If:
P1= 12x^2-6xy+9y^2
P2= -2x^2+3xy-4y^2
P3= 2x-y^2

And:
M1= -3xy

1) P3-P2

=(2x-y^2)-(-2x^2+3xy-4y^2)
=(2x-y^2)+(2x^2-3xy+4y^2)
=2x+(-y^2+4y^2)+2x^2-3xy
=2x+3y^2+2x^2-3xy

2) P2XP3

=(-2x^2+3xy-4y^2) (2x-y^2)
=(-2x^2)x2x+(-2x^2)x(-y^2)+3xyx2x+3xyx(-y^2)+(-4y^2)x2x+(-4y^2)x(-y^2)
=(-4x^3)+2x^2y^2+6x^2y-3xy^3-8xy^2+4y^4

3)P1/M1

=12x^2-6xy+9y^2
----------------
-3xy
=12x^2 -6xy 9y^2
------ + ----- + ------
-3xy -3xy -3xy

=-4xy^-2+0.5+-3x^-1y
=-4xy^-2-x^-1y+0.5
=-7x^-1y^-1+0.5
=0.5
----
7xy

Those are the first three, I'm trying my best not to check everything with you guys because the homework is extensive and I've already had to ask for a prolongation, which cost me 60$more (on top of the 350$+ they charged for the class), so believe me when I say that this is important for me and you guys are not wasting your time helping me out.

Thank you so much

Neenoon

2. First two are correct. I'm not sure what you wrote in the last one, but here it is anyways:

$\frac{12x^2 - 6xy + 9y^2}{-3xy}$

$= \frac{-12x^2 + 6xy - 9y^2}{3xy}$

$= \frac{-12x^2}{3xy} + \frac{6xy}{3xy} - \frac{9y^2}{3xy}$

$= -\frac{4x}{y} + 2 - \frac{3y}{x}$

$= -4xy^{-1} + 2 - 3yx^{-1}$

P.S. You brain works just as good as before, if not better.

3. Originally Posted by Neenoon

If:
P1= 12x^2-6xy+9y^2
P2= -2x^2+3xy-4y^2
P3= 2x-y^2

And:
M1= -3xy

1) P3-P2

=(2x-y^2)-(-2x^2+3xy-4y^2)
=(2x-y^2)+(2x^2-3xy+4y^2)
=2x+(-y^2+4y^2)+2x^2-3xy
=2x+3y^2+2x^2-3xy
This is correct.

Originally Posted by Neenoon
2) P2XP3

=(-2x^2+3xy-4y^2) (2x-y^2)
=(-2x^2)x2x+(-2x^2)x(-y^2)+3xyx2x+3xyx(-y^2)+(-4y^2)x2x+(-4y^2)x(-y^2)
=(-4x^3)+2x^2y^2+6x^2y-3xy^3-8xy^2+4y^4
This is correct too.

Originally Posted by Neenoon
3)P1/M1

=12x^2-6xy+9y^2
----------------
-3xy
=12x^2 -6xy 9y^2
------ + ----- + ------
-3xy -3xy -3xy

=-4xy^-2+0.5+-3x^-1y
=-4xy^-2-x^-1y+0.5
=-7x^-1y^-1+0.5
=0.5
----
7xy
Here I got:

$-4xy^{-1} + 2 -3x^{-1}y$

4. Thank you so much, I was a bit off on that last one. I think I get it now (oh, and I'll trying doing whatever you are doing to post the equation so that they are more readable).